Maternal Mortality During the Corona Virus Disease-19 (COVID-19) Pandemic - Purnamawati, Dewi; Andriyani, Andriyani; Wulandari, Wulandari (Fakultas Kesehatan Masyarakat Universitas Muslim Indonesia, 2023)
The COVID-19 pandemic poses a risk of increasing morbidity and mortality in pregnant women. Pregnant women have a higher case fatality rate and more complications than non-pregnant women due to COVID-19 infection. This study aims to look in depth at maternal deaths during the COVID-19 pandemic at the Karawang District Hospital. This study used a qualitative approach with a case study design. Cases were defined as the deaths of pregnant women during the COVID-19 pandemic period recorded at the Karawang District Hospital as many as 5 cases. involving 13 informants consisting of 5 case family information and eight midwife informants. Data were collected using in-depth interviews, which were carried out by applying health protocols. Data were analyzed descriptively using thematic analysis. This study resulted in four themes: case characteristics, antenatal examination, referral process, and causes of maternal mortality. The results showed that all cases had risk factors in pregnancy. Almost all cases do not undergo regular antenatal checks due to fear and posyandu services that were not available during the COVID-19 pandemic. All cases have delayed conditions in the referral process, such as early detection, decision-making, and delayed arrival at health facilities due to road access and transportation. Another thing that causes delays is waiting for the results of the rapid test to come out of the primary healthcare facility. The cause of maternal death during the COVID-19 pandemic at the Karawang District Hospital does not seem different from before the COVID-19 pandemic, which is complications in pregnancy. It is necessary to increase efforts for early detection of complications by increasing public knowledge and capacity of midwives and improving the referral flow system, especially during the COVID-19 pandemic.